PENGARUH BRAND IMAGE, STORE IMAGE, DAN ADVERTISING TERHADAP PERILAKU PEMBELIAN PRODUK MS GLOW STORE ADELIA DI KOTA BATAM - Nurhabsyina Nurhabsyina; Hikmah Hikmah (LPPM Universitas Putera Batam, 2026)
This research aims to examine the influence of brand image, store image, and advertising on the purchasing behavior of MS Glow products at Adelia Store in Batam City. The population used is users who have used MS Glow products at Adelia Store, with a predetermined number based on monthly consumer data. The sampling technique uses the Slovin formula with a calculation of 189 respondents using purposive sampling technique. Data were analyzed using multiple linear regression models, with data quality testing, classic assumption testing, influence testing, and hypothesis testing. The results of multiple linear regression analysis show that brand image has an influence of 14.5% on purchasing behavior of MS Glow products at Adelia Store in Batam City. Store image has an influence of 30.2% on purchasing behavior of MS Glow products at Adelia Store in Batam City. Advertising has an influence of 63.1% on purchasing behavior of MS Glow products at Adelia Store in Batam City. The findings using the coefficient of determination (R2) show that brand image, store image, and advertising have an influence of 74.6% on purchasing behavior of MS Glow products at Adelia Store in Batam City. In addition, t-test and F-test show that brand image, store image, and advertising, both individually and collectively, have a positive and significant influence on the purchasing behavior of MS Glow products at Adelia Store in Batam City.